Psychological Peculiarities of the Preschool Age Children with Speech Violations - Komisaryk, Mariya; Kuznietsova, Kateryna (Lumen, 2021)
It is concluded that the study of the basics of speech therapy is necessary for all staff of preschool institutions in order to timely notice the language disorder of preschool children and quickly and efficiently overcome it. This will contribute to the better assimilation of knowledge by the child, the manifestation of his creative abilities, adaptation in society, optimization of mental development of the child as a whole
Keywords: speech therapy, speech disorders, dyslalia, preschooler, preschool institutions, speech therapist